Dampak Liberalisasi Perdagangan Terhadap Kinerja Industri Manufaktur di Indonesia (Pendekatan Structure-Conduct-Performance) - Hendy Aprilian Hidayat; Alfa Farah (Jurnal Ekonomi dan Bisnis, 2015)
The influx of imported goods in the domestic market will pressure domestic producers to be more efficient. The more effiecient the domestic firm, the more competitive it becomes. This competitive firm is expected to have opportunities to expand to a larger market. This study analyzed the effect of trade liberalization to industrial performance in Indonesia. This study exploited data at the industry level, ie: 38 industries of three digits International Standard Industrial Classification (ISIC) during 2000-2009. The analysis was conducted within Structure Conduct Performance (SCP) framework. Industrial performance was measured by price-costmargin and trade liberalization was measured by export share and a dummy indicating implementation of Asean Free Trade Area (AFTA). Using the fixed effect model, the result showed weak evidence of the effect of trade liberalization to industrial performance in Indonesia. Dummy AFTA was negative and significant to industrial performance while export share was insignificant. The results might indicate that the adoption of AFTA endangered domestic firms’ performance.